Odpowiedzi

Najlepsza Odpowiedź!
2009-11-16T21:06:36+01:00
F(x)=2x+3
f(n+1)-f(n)=2(n+1)+3-2n-3=2n+2-2n=2
lim[f(n+1)-f(n)]=2 gdy n→∞
-----------------------------------------
f(x)=1/(2x+3)
f(n+1)-f(n)=1/[2(n+1)+3]-1/(2n-3)=
1/(2n+5)-1/(2n-3)=[2n-3-2n-5]/[(2n+5)(2n-3)]=
-8/[(2n+5)(2n-3)]
lim[f(n+1)-f(n)]=0 gdy n→∞
--------------------------------------------
f(x)=x²
f(n+1)-f(n)=(n+1)²-n²=(n+1-n)(n+1+n)=2n+1
lim[f(n+1)-f(n)]=∞ gdy n→∞
------------------------------------------------
f(x)=√x
f(n+1)-f(n)=√(n+1)-√n
lim[f(n+1)-f(n)]=?

przeksztalce w/w na postac ulamkowa /pseudo uwymiernianie/
mnoze licznik i mianownik przez sume
[√(n+1)-√n]/1=[n+1-n]/[√(n+1)+√n]=1/[√(n+1)+√n]
lim[f(n+1)-f(n)]=0 gdy n→∞

Pozdrawiam

ciekawe zadanie

jezeli masz odpowiedz to prosze
napisz do mnie

Hans





1 5 1